Le Parc des Caudreleux, malgré lui. Une défense et une illustration du concept de métaprojet - Denis Delbaere (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère, 2021)
This paper deals with the failure of projects in the case of landscape architecture. Considering the specific way that time transforms open spaces, the author presents the concept of metaprojet in order to think of a projects’ continuity after its realization and through the role of actors who appropriate the space. The paper focuses on a park designed by the author himself, who describes its design, its building and its alteration over a period of twenty years. He shows the theoretical basis of his dissertation, in the field of anthropology, archaeology and landscape ecology, in order to give a scientific framework to the kind of critical studies he reclaims.